The Potential of CRISPR/Cas9 Gene Editing as a Treatment Strategy for Inherited Diseases - Abdelnour, Sameh A.; Xie, Long; Hassanin, Abdallah A.; Zuo, Erwei; Lu, Yangqing (Frontiers in Cell and Developmental Biology, 2021)
Clustered regularly interspaced short palindromic repeats (CRISPR) approaches a hopeful innovative technology for genomic editing that offers scientists the chance to effortlessly modify DNA structures and loss of genomic function. It has several possible intentions consist of rectifying inherited deficiencies, treating and avoiding the spread of disorders. Recently, reports have demonstrated that inventing synthetic RNA molecules and supplying them alongside with Cas9 into genomic of eukaryotic, since distinct specific regions of the genome can be manipulated and targeted. The therapeutic potential of CRISPR/Cas9 technology is great, especially in gene therapy, in which a patient-specific mutation is genetically adjusted or remedying human disorders that are untreatable with traditional treatments. This review focused on numerous, in vivo, in vitro and ex vivo uses of the CRISPR/Cas9 technology in human disease-concentrated exploration, discover the capability of this versatile in medicine and examine some of the main limitations for its upcoming use in patients. In addition to introduce brief impression of the biology of the CRISPR/Cas9 scheme and its mechanisms, we assembled the utmost recent discoveries on the uses of CRISPR/Cas9 technology for clearer explorations of the inherited and rectifying of human genetic diseases.